STABILITY RESPONSES FOR QUALITY TRAITS IN POTATO (SOLANUM TUBEROSUM L.) - SANWAL, S K.; BHUTANI, R D; KHURANA, S C (Potato Journal, 2013)
Adaptation of a variety over a wide range of environments has considerable significance in crop improvement programme particularly in potato, which is oftenly cultivated under diverse climatic conditions. Twenty seven genotypes of potato were grown during the crop seasons of 1999-2000 and 2000-2001, planted on 6th, 26th October and 15th November (both years), thus making a total of six environments on the research farm at Hisar. Under each environment, 3.5 meter long single row of each of these genotypes was planted at a spacing of 60 x 20 cm in a randomized block design with three replications. The crop was harvested at 105 days after planting. The data were analysed statistically for stability parameters in respect of dry-matter content, reducing sugars, total sugars, protein content and starch content. Both linear and non-linear components of variations were significant, with the preponderance of linear component. Therefore, prediction for most of the genotypes appeared to be feasible for these traits. Based on desired mean values (high/low) and stability parameters, the genotypes Kufri Chipsona-2, Kufri Badshah, Kufri Jawahar and JX-216 for dry-matter content; Kufri Chipsona-1 and Kufri Chipsona-2 for reducing sugars; Kufri Chipsona-1, Kufri Sutlej, Kufri Bahar and Kufri Ashoka for protein content and JX-216, JW160 and Kufri Chipsona-2 for starch content were found suitable for all types of environments. However, planting of potato crop in the last week of October has been found beneficial for improving quality traits (dry-matter content, starch content, reducing and total sugars) of potato tubers, based on environmental index values.